Gary D. Wymore letter to Nicholas S. Halmi regarding bird sightings, January 30, 1977 - Wymore, Gary D.et al (1977)
Bird sightings contributed by Gary D. Wymore in a letter to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1976-1977. Epson - sheet feed/flatbed